ZULFIYA AND PEDAGOGICS: THE IMPORTANCE OF HER POEMS IN SHAPING THE YOUNGER GENERATION - G`ulomova Sh.X. (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Zulfiya Murodova is a significant figure in Uzbek literature, known for her contributions as a poet, prose writer, and translator. Her writings are distinguished not only by their artistic beauty but also by their profound psychological insights. In her work, Zulfiya delves into the human psyche, exploring the inner worlds, emotions, and personalities of her characters in a distinctive manner. This article examines the psychological profiles and inner landscapes of characters portrayed in Zulfiya's literature.